Creating a new paradigm for the local interstellar medium–A perspective - Linsky, Jeffrey L.; Redfield, Seth (Frontiers in Astronomy and Space Sciences, 2023)
The interstellar medium close to the Sun called the local ISM (LISM) provides critical insights into physical processes and phenomena in the more distant interstellar medium in our Galaxy without the confusion of many complex structures in the sight lines to distant stars. High-resolution ultraviolet spectra are powerful diagnostic tools for understanding the LISM together with the observed properties of the outer heliosphere and hydrogen wall absorption in the astrospheres of nearby stars. For nearly 30 years the kinematic structure of the LISM has been identified from measured radial velocities of interstellar gas along many sight lines distributed across a wide range of Galactic coordinates. These data permitted the identification of three dimensional velocity vectors characterizing ``clouds". While this simple structure robustly predicts the radial velocities and associated clouds along newly observed sight lines, there are many challenges to this multi-cloud model that could lead to a revised model of the LISM. This paper reviews the assumptions and accomplishments of the multi-cloud model, and describes how the various challenges to this model could lead to a more comprehensive model with insight into physical processes and structures in the Galactic interstellar medium.